2010
DOI: 10.1136/vr.c3811
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a PCR assay in whole blood and serum specimens for canine brucellosis diagnosis

Abstract: The performance of a serum PCR assay was compared with that of a blood PCR assay for the diagnosis of canine brucellosis caused by Brucella canis in 72 dogs. The dogs were classified into three groups (infected, non-infected and suspected brucellosis) according to the results of blood culture and serological tests. The sensitivities of blood PCR and serum PCR were, respectively, 97.14 per cent and 25.71 per cent. The specificities of both were 100 per cent. In the group of dogs with suspected brucellosis, thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
15
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 18 publications
2
15
0
Order By: Relevance
“…O'Leary et al [31] suggested that since bacteria are taken up by macrophages and non-professional phagocytes, white blood cells templates might be worthy templates for use in PCR detection. In addition, similar results where DNA was extracted from blood and used in screening animals for brucellosis were documented by Madboly et al [33] in buffalo, Keid et al [34] in dogs and Khamesipour et al [21] in cattle and sheep. The identification of Brucella spp.…”
Section: Discussionsupporting
confidence: 69%
“…O'Leary et al [31] suggested that since bacteria are taken up by macrophages and non-professional phagocytes, white blood cells templates might be worthy templates for use in PCR detection. In addition, similar results where DNA was extracted from blood and used in screening animals for brucellosis were documented by Madboly et al [33] in buffalo, Keid et al [34] in dogs and Khamesipour et al [21] in cattle and sheep. The identification of Brucella spp.…”
Section: Discussionsupporting
confidence: 69%
“…Studies have demonstrated that in dogs with reproductive problems or naturally infected by B canis, the identification of this pathogen by PCR using vaginal swabs or semen samples is more sensitive comparable to the utilization of PCR derived from blood or serum samples (KEID et al, 2007). Additionally, the utilization of serum samples of infected dogs for the diagnosis of B canis by PCR is of restricted diagnostic value (KEID et al, 2010).…”
mentioning
confidence: 99%
“…To resolve this problem, a variety of molecular genetics techniques have been introduced as follows; PCRs to amplify the gene encoding the 31 kDa Brucella cell surface protein (BCSP31), the gene encoding the Brucella outer membrane protein (OMP2), and the 16-23S ribosomal RNA interspace region (ITS), 16S rRNA and BaSS [24][25][26][27]. These PCR assays, except for BaSS, can detect Brucella only at the genus level [28].…”
Section: Discussionmentioning
confidence: 99%